SME DEVELOPMENT STRATEGY AS THE FOUNDATION OF THE NATIONAL ECONOMY - Teguh Setiawan Wibowo; Nurul Hidayati; Endri Haryati (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
With the dynamic dynamics of the global economy, Indonesia as a developing country with a large population is facing challenges and emerging opportunities in managing the national economy. To anticipate this, the national economic foundation in Indonesia needs to be strengthened, especially the entrepreneurial factor, such as the development of SMEs. The aim of the research is to analyze the development strategies of SMEs as the foundation of the national economy. The research method used a qualitative method supported by literature studies (books, journals and the internet). The results are 5 strategies that can be implemented to develop SMEs as the foundation of the national economy, such as development strategy of SMEs in the free market sector, development strategy of SMEs in the role and government policy sector, development strategy of SMEs in the competitive human resources sector, development strategy of SMEs in the physical capital sector and strategic development of SMEs in the entrepreneurial sector. By implementing strategies in these sectors, SMEs will be able to become the backbone of the local economy, increasing employment opportunities for local communities, reducing unemployment rates and increasing the economic productivity of society in Indonesia as a whole